Effect of Anthropogenic Aerosol Addition on Phytoplankton Growth in Coastal Waters: Role of Enhanced Phosphorus Bioavailability - Wang, Qin; Zhang, Chao; Jin, Haoyu; Chen, Ying; Yao, Xiaohong; Gao, Huiwang (Frontiers in Microbiology, 2022)
Atmospheric deposition can supply nutrients to induce varying responses of phytoplankton of different sizes in the upper ocean. Here we collected surface and SCM (subsurface chlorophyll a maximum) seawaters from the Yellow Sea and East China Sea to conduct a series of onboard incubation experiments, aiming to explore the impact of anthropogenic aerosol (AR, sampled in Qingdao, a coastal city in Northern China) addition on phytoplankton growth using schemes with (unfiltered seawater, UFS) and without (filtered seawater, FS) microsized (20–200 μm) cells. We found that AR addition stimulated phytoplankton growth obviously, as indicated by chlorophyll a (Chl a) in surface incubations, and had stimulatory or no effects in SCM incubations, which was related to nutrient statuses in seawater. The high ratio of nitrogen (N) to phosphorus (P) in the AR treatments demonstrated that P became the primary limiting nutrient. The alkaline phosphatase activity (APA), which can reflect the rate at which dissolved organic P (DOP) is converted into dissolved inorganic P, was 1.3–75.5 times higher in the AR treatments than in the control, suggesting that AR addition increased P bioavailability in the incubated seawater. Dinoflagellates with the capacity to utilize DOP showed the dominant growth in the AR treatments, corresponding to the shift in phytoplankton size structure towards larger cells. Surprisingly, we found that nanosized (2–20 μm) and picosized (0.2–2 μm) Chl a concentrations in UFS were generally higher than those in FS. The APA in UFS was at least 1.6 times higher than in FS, and was proportional to the contribution of microsized cells to the total Chl a, suggesting that microsized cells play an important role in the increase in APA, which contributes to the growth of nanosized and picosized phytoplankton. Current work provides new insight into the increase of P bioavailability induced by atmospheric deposition and resultant ecological effect in coastal waters.